PENGARUH KELOMPOK RUJUKAN TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MEREK WARDAH (STUDI KASUS MAHASISWI DI PEKANBARU) - Marroaini, Marroaini (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the influence of referral groups on purchasing decisions for Wardah brand cosmetics among female students in Pekanbaru. To achieve this goal, research was carried out on a sample of 94 female students. The analysis model used is the Multiple Regression Analysis model, while testing the hypothesis using statistical tests, namely the F test, t test, and determination test (R2), Based on the results of the analysis described in the discussion, it is proven that not all variables in the reference group can influence the decision to purchase Wardah brand cosmetics. Based on Fcount statistics, it shows that simultaneously or not, the variables of friendship groups, shopping groups, work groups, virtual community groups, and consumer activist groups influence the purchasing decisions of Wardah brand cosmetics for female students in Pekanbaru. The Consumer Activist Group variable has a dominant influence on the decision to purchase Wardah brand cosmetics for female students in Pekanbaru